2006
DOI: 10.1111/j.1440-1681.2006.04446.x
|View full text |Cite
|
Sign up to set email alerts
|

JWA IS REQUIRED FOR THE ANTIPROLIFERATIVE AND PRO‐APOPTOTIC EFFECTS OF ALL‐TRANS RETINOIC ACID IN HELA CELLS

Abstract: 1. All-trans retinoic acid (ATRA) is known to inhibit cellular proliferation and induce differentiation and apoptosis. It usually activates gene expression by binding to a nuclear receptor that interacts with retinoic acid-response elements (RARE) and then activates the mitogen-activated protein kinase signal pathway. JWA, a newly identified ATRA-responsive gene, has recently been proposed as an important molecule for cellular differentiation induced by some chemicals, including ATRA. 2. To investigate the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…In addition to our analyses, a paper by Mao et al has shown that all-trans retinoic acid inhibits proliferation and causes apoptosis through the activation of ARL6IP5 and that this activation is mediated by C/EBPα through direct binding to the promoter of ARL6IP5 [21]. Therefore, we suggested that the ARL6IP5 gene might be a key protein which mediates pro-apoptotic activity of C/EBPα in NIH3T3 cells and have investigated the role of ARL6IP5 in proapoptotic activity of C/EBPα.…”
Section: C/ebpα Activates Apoptotic Pathways and Diminishes Expressiomentioning
confidence: 88%
See 1 more Smart Citation
“…In addition to our analyses, a paper by Mao et al has shown that all-trans retinoic acid inhibits proliferation and causes apoptosis through the activation of ARL6IP5 and that this activation is mediated by C/EBPα through direct binding to the promoter of ARL6IP5 [21]. Therefore, we suggested that the ARL6IP5 gene might be a key protein which mediates pro-apoptotic activity of C/EBPα in NIH3T3 cells and have investigated the role of ARL6IP5 in proapoptotic activity of C/EBPα.…”
Section: C/ebpα Activates Apoptotic Pathways and Diminishes Expressiomentioning
confidence: 88%
“…This target is the ARL6IP5 protein which has been previously characterized as an inducer of apoptosis in cultured cells. The promoter region of the ARL6IP5 gene contains two binding sites for C/EBP proteins and potentially might be regulated by C/EBP proteins [21]. Given the ubiquitous expression of another member of C/EBP family, C/EBPβ, one would assume that the ARL6IP5 promoter might be active in many cell types.…”
Section: Apoptotic Activities Of C/ebpαmentioning
confidence: 99%
“…The PRAF2-related protein PRAF3 (JWA/GTRAP3-18) was recently implicated in the regulation of retinoic acid-induced cell differentiation, cell migration, and apoptosis in various cancer types, including leukemia and cervical cancer (23)(24)(25)(26)(27). These findings prompted us to examine whether PRAF2 plays a role in neuroblastoma apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…JWA, a novel signaling molecule, has been reported to be associated with cell differentiation, growth inhibition, and apoptosis induction mediated by ATO, ATRA, and 12-Otetradecanoylphorbol 13-acetate in human malignant cells including myeloid leukaemia cell lines and primary cultured APL blasts [112][113][114]. Recently, Zhou et al reported that JWA is required for ATO induced apoptosis in HeLa and MCF-7 cells via ROS and mitochondria linked signal pathways [115].…”
Section: Ato-induced Apoptosis Mediated Through Other Moleculesmentioning
confidence: 99%